Ultrasensitive biosensors based on waveguide-coupled long-range surface plasmon resonance (WC-LRSPR) for enhanced fluorescence spectroscopy. Issue 36 (25th June 2021) - Thi Tran, Nhu Hoa; Phung, Viet-Duc; Thi Ta, Hanh Kieu; Lam, Vu Dinh; Manh, Do Hung; Pham, Ngoc Kim; Kim, Jae Young; Lee, Nae Yoon; Phan, Bach Thang
Abstract : We investigated the coupling phenomenon between plasmonic resonance and waveguide modes through theoretical and experimental parametric analyses on the bimetallic waveguide-coupled long-range surface plasmon resonance (Bi-WCLRSPR) structure. Abstract : We investigated the coupling phenomenon between plasmonic resonance and waveguide modes through theoretical and experimental parametric analyses on the bimetallic waveguide-coupled long-range surface plasmon resonance (Bi-WCLRSPR) structure. The calculation results indicated that the multi-plasmonic coupling gives rise to the enhanced depth-to-width ratio of the reflection dip compared to that of LRSPR excited using a single set of Ag and Teflon. The optimized thickness of Ag(40 nm)/Teflon(700 nm)/Ag(5 nm)/Au(5 nm) was obtained and generated the highest plasmon intensity enhancement, which was 2.38 folds in comparison to the conventional bimetallic surface plasmon resonance (SPR) configuration (Ag/Au). 17β-Estradiol was used in the fluorescence enhancement experiment by the reflection geometry-based system, wherein the excitation light source was on the side of a WC-LRSPR chip opposite to that of the light detection unit. The phenomenon of surface plasmon-couple emission (SPCE) depends on the number of 17β-estradiol molecule promoters from female sex steroid hormones, which demonstrated a limit of detection (LOD) of 2 pg mL −1 and 1.47-fold fluorescence improvement as compared to the non-coated material on the surface of pristine glass. This enhanced WC-LRSPR can readily find application in fluorescence escalation needed in cases where a weak fluorescence signal is predicted, such as the small volume of liquid containing fluorescent dyes in biological diagnosis.